PENATALAKSANAAN GIZI DALAM PENYAKIT BERBASIS GENETIK (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The world of nutrition and health has developed very rapidly in the last two decades. Developments in science and technology driven by advanced analysis and interventions in the biomedical field are now penetrating the world of nutrition. The development of science and services in the field of nutrition should move along with technological developments. Nutrition services that initially relied on anthropometric, biochemical, clinical and dietary intake examinations can now move on to utilizing new analytical methods, one of which is genetics.Along with the growing market need for a complete, precise and personalized healthcare system, genetic screening is now starting to develop. The principle is that each person carries a genetic variation that is different from one another and it is this factor that makes them unique. This uniqueness impacts differences in disease risk and response to food and medication. For example, while some of us have no problem consuming milk and dairy products, others do and this is often referred to as lactose intolerance. A series of studies show that the possibility of lactose intolerance is influenced by genetic factors that a person carries. By undergoing genetic testing, we can find out our response to food/nutrients so that our quality of life can be improved.The development of genetic testing services that were initially initiated by several start-up companies in the United States is now reaching various parts of the world with different adaptations in each line. Indonesia is expected not to be left behind in this part of the biotechnology industry in Health services. Several laboratory analysis service providers are now starting to provide genetic examinations and present the field of Nutrigenetics in the midst of Indonesian society. The science of nutrigenetics can now be applied in the clinic and can help improve the quality of life for many people. This genetic data-based nutritional counseling service is expected to increase the competence of nutritionists and dietitians in accordance with scientific and technological developments and consumer needs.